Nanometric gold in cancer nanotechnology: current status and future prospect. (24th December 2012) - Ahmad, Mohammad Zaki; Akhter, Sohail; Rahman, Ziyaur; Akhter, Shabib; Anwar, Mohammed; Mallik, Neha; Ahmad, Farhan Jalees
Abstract: Objectives: This review elaborate on modified gold nanoparticulate concept in oncology, provides an overview of the use of gold nanoparticles in cancer treatment and discusses their potential applications and clinical benefits. Key findings: Modified gold nanoparticles (e.g. rod, multipod and star or a hollow structure such as shell, box and cage) have promising applications in the fields of drug delivery and photothermal therapy in oncology due to their unique optical and photothermal properties and their ability to modify the surface and conjugate drugs/molecules with gold nanomaterial. Modified gold nanoparticles exhibit strong light absorption in the near‐infrared region in which light can penetrate deeply into soft tissue. Moreover, recent advances have opened the way to site‐specific delivery by gold nanoparticle. Summary: Recent research and development in cancer‐targeted gold nanovectors shows promise for maximizing the efficacy of anti‐cancer drugs while decreasing their harmful systemic effects in chemotherapy. Moreover, gold nanoparticles can also serve as cancer therapeutic.